Islamic Business Ethics in Online Secondhand Clothing Sales: A Case Study of Fuka Project Store Based on Fiqhul Islam wa Adillatuhu - Lutfiyatul Azizah; Enjen Zaenal Mutaqin (Wealth: Journal of Islamic Banking and Finance, 2025)
Technological developments have encouraged the rise of online thrift buying and selling practices, which are considered economical and environmentally friendly. However, this phenomenon raises ethical issues, especially related to transparency and honesty in transactions. This study aims to evaluate the suitability of the buying and selling practices carried out by the Fuka Project Store through the Shopee platform with the principles of Islamic business ethics based on the book Fiqhul Islam wa Adillatuhu by Wahbah Az-Zuhaili. This study uses a qualitative method with a literature study approach and field research through observation and interviews. The results of the study indicate that the buying and selling practices in the store have reflected several principles of Islamic ethics, such as honesty, fairness, and the use of original product photos. However, there are still shortcomings in terms of product information that is not detailed enough, and the application of the principles of responsibility and transparency is not optimal. An increase in understanding and application of Islamic business ethics values is needed so that online buying and selling practices are not only valid according to sharia but also bring blessings and public trust.